LITERATUR REVIEW: KONSELING KELOMPOK UNTUK MENINGKATKAN HARGA DIRI REMAJA - Sayyida Aulia Salsabila; Syaifatur Rohmah; Anggraeni Putri Larasati (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2025)
Adolescence is a crucial period in life when many things change significantly, including an individual's self-esteem. The purpose of this study was to investigate how well group counseling can improve adolescent self-esteem. Literature review is the methodology used, which requires a critical evaluation of various related literature sources, such as books, journal articles, and previous research findings. The analysis obtained shows that group counseling, using various strategies such as role-playing, journaling, assertive training, and cognitive restructuring, can significantly improve adolescent self-esteem. Adolescents can share experiences and receive social support in a safe environment through group counseling, which increases their self-confidence. Based on the results of the study, group counseling is a useful intervention to improve adolescent self-esteem, so it needs to be widely used in the context of guidance and counseling services.